Analysis of lightning flash rate with the occurrence of flash floods and hailstorms in Peninsular Malaysia - Mohd Esa, Mona Riza; Bahari, Noraishah; Mohammad, Sulaiman Ali; Ahmad, Mohd Riduan; Ahmad, Noor Azlinda; Abdul Malek, Zulkurnain (Elsevier, 2023)
This paper will present five flash flood cases in Johor and two hailstorms from Kuala Lumpur and Melaka reported during lightning activities to determine the relationship between lightning flash rate and rainfall that occurred from 2013 to 2017. The flash floods were observed based on lightning data obtained from Tenaga Nasional Berhad Research Sdn. Bhd. (TNBR) and rainfall data from the Department of Irrigation and Drainage (DID). On the other hand, storm-producing hails were observed based on the lightning flash rate using electromagnetic field measurements and weather radar for their reflectivity value and cloud structure. The detection of a lightning flash, especially the negative narrow bipolar event (− NBE) and positive cloud-to-ground (+CG), could be a possible indicator of a deeper convective storm that could lead to the production of hails. In the 24-h observation of selected days when a flash flood occurred, lightning strikes correlation with rainfall had r-values ranging from 0.6 to 0.9, where the lightning data may enhance flood forecasting accuracy when combined with rainfall. Meanwhile, during the first hailstorms in Kuala Lumpur, the highest − NBEs flash rate detected during the hails appeared where 16 − NBEs were detected in a span of 5 min with reflectivity value between 53 and 55 dBz and cloud top height of 20 km. During the second hailstorms in Melaka, more + CG flashes rather than − NBE were detected during the appearance of the hail, with 64 +CG flashes and five − NBEs with reflectivity values between 60 and 66 dBz and cloud top height of 18.8 km. Based on the high convective strength, cloud top height, and presence of hailstones, − NBE and +CG flash could be possible indicators of storm severity, especially in Malaysia.